Islam: Ideal and Reality (Czech Journal of International Relations, 1992)
Under this title, another publication of a group of workers of the CSAV Oriental Institute, dealing with this highly topical issue, was published. Reviewed the book represents the logical culmination of the efforts of our most professional scientific workplace to bring the various aspects and spheres of influence of this world religion closer to the Czech reader. After the previously published books/ which showed how Islam influenced and still influences to a considerable extent the sphere of politics and the place of Muslim states in the world, the authors of the current publication took the step that is probably the most necessary from the point of view of our public, to comprehensively shed light on Islam by itself. It is necessary to say at the outset that they succeeded. The reader got his hands on a book that presents the basic characteristics of Islam in a readable form, explains the main concepts, brings Islamic institutions closer to it, etc. At the same time, the author's collective is based not only on theory and what is written, but also on practice and how the regulations of Islam are practically applied. In this regard, the subtitle of the book Ideal and Reality is really justified. The authors managed to capture different interpretations of the regulations, although they did not get bogged down in excessive details.